Novel systemic treatments in atopic dermatitis: Are there sex differences? - Katherine L. Tuttle, MD; Jessica Forman, MA; Lisa A. Beck, MD (Wolters Kluwer, 2021)
Atopic dermatitis (AD) is a common inflammatory skin disease with a significant global disease burden. Several mechanisms underlie AD, such as epidermal barrier dysfunction and immune dysregulation, which have led to innovative systemic treatment options. Other inflammatory disorders, as well as innate and adaptive immune responses, have noted sex differences, but our article highlights a paucity of data on the impact of sex, gender, and gender identity on the pathophysiology and systemic treatments of AD.